Städte und Europäische Strukturpolitik - Eltges, Markus (Raumforschung und Raumordnung | Spatial Research and Planning, 2005)
Since the beginning of the 1990’s the European institutions have discovered the theme area “city and urban development” for themselves. Particularly the European Union and here especially the European Commission with its structural policy are dealing with the subject. The main concern of the European Union is the support of the development of integrated concepts for urban development. The previously traditional sector-specific approach and the distribution of competence and responsibilities at different decision-making levels that is associated with this has made the solution of urban problem situations more difficult. The entire European economy is suffering from this. Particularly with the AGENDA 2000 urban promotion contents have increased in importance. With the reform of the structural funds this urban development policy dimension is to experience a further revaluation after 2006 according to the intention of the Commission. Urban development is to become an explicit component of regional policy, in order to contribute to the achievement of the Lisbon objectives in this way.